Executive power in the European Union : law, practices, and the living constitution - Curtin, Deirdre (Oxford : Oxford University Press, 2009)
The picture of Brussels-based bureaucrats exercising arbitrary executive powers is one of the favourite images conjured by Eurosceptics across the political spectrum. This book offers a richer understanding of the nature of the EU's powers, how they relate to national governments, and how they are controlled.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Executive power -- European Union countries; Administrative law -- European Union countries